Dynamics of nutritional food consumption and expenditure patterns of Central Java population as welfare indicators to achieve sustainable development goals. Issue 1 (November 2021) - Rahayu, W; Darsono; Marwanti, S; Antriyandarti, E
Abstract: This study aims to determine Central Java population welfare dynamics by looking at the pattern of expenditure and the nutritional and food consumption level. The data used is data on the expenditure and consumption of the Central Java population in 2016–2020. The data analysis method used is descriptive analytical. The study of expenditure patterns shows that during the period 2016–2020, the Central Java population welfare is increasing. Still, the population of rural areas is less prosperous than the population of urban areas. The welfare increase is also shown by decreasing the cereals group consumption. The analysis of the nutritional consumption level indicates that the energy and protein consumption level tend to increase during 2016–2020. The level of energy consumption is categorized as sufficient, and protein consumption level is categorized as good. In rural areas, energy consumption and energy consumption are higher than in urban areas; conversely, protein consumption and protein consumption in urban areas are higher than in rural areas.